LI-RADS CT/MRI Treatment Response Assessment Update in 2024 - Jaeseung Shin; Kyowon Gu; Ji Hye Min (Journal of the Korean Society of Radiology)
The liver imaging reporting and data system (LI-RADS) CT/MRI treatment response assessment (TRA) provides a standardized framework for evaluating treatment response following loco-regional therapy for hepatocellular carcinoma (HCC). Initially introduced in 2017, it was revised in 2024 to reflect advances in research. The updated LI-RADS CT/MRI TRA v2024 presents a bifurcated algorithm based on the mechanisms underlying loco-regional therapy and introduces distinct assessment criteria with which to evaluate treatment response after radiation therapy. Furthermore, ancillary imaging features, including diffusion restriction and mild-to-moderate T2 hyperintensity, have been incorporated as optional adjuncts to refine the assessment of viable tumors. The effective implementation of the LI-RADS CT/ MRI TRA v2024 is anticipated to enhance treatment response assessment following loco-regional therapy for HCC. Further research is encouraged in order to ensure the continuous refinement and optimization of the assessment criteria.